Developing Countries and the Globalization of Financial Markets - Knight, Malcolm (IMF Working Papers; Working Paper, 1998)
This paper analyzes the impact of the globalization of financial markets on developing and transition economies. Differences between the responses of competitive and imperfectly competitive banking sectors cause them to affect economic activity differently. While nonbank financial markets and institutions can help to increase the competitiveness of banking sectors, there are 'gaps' in the institutions and market structures of developing and transition economies. Eliminating these gaps may reinforce financial market discipline in these countries. Some current international initiatives are outlined for enhancing financial system soundness; these emphasize the complementary roles of market discipline and official oversight in an environment of globalized markets.